2017
DOI: 10.1177/1750481317699432
|View full text |Cite
|
Sign up to set email alerts
|

Humour and laughter in meetings: Influence, decision-making and the emergence of leadership

Abstract: Recent constructions view leadership as a process of social influence which coordinates processes of change. Moreover, such processes are not necessarily linked to role hierarchy but may be emergent and distributed within teams. However, the micro-processes through which this occurs are not well understood. The significance of the paper lies in its contribution to an understanding of the emergence of leadership in teams, and in particular how humour and laughter are drawn on as a resource by which to exert soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Finally, humour can function as a facilitator of social conflict, allowing expression of opposition, resistance, and dissent (Mulkay 1988). Humour can be used to reinforce a position in the group (Watson and Drew 2017). It also offers the speaker the opportunity to take a position of superiority, allowing an attack on others in a socially-acceptable way or enhancing self-esteem at the expense of others (Rodrigues and Collinson 1995).…”
Section: Humourmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, humour can function as a facilitator of social conflict, allowing expression of opposition, resistance, and dissent (Mulkay 1988). Humour can be used to reinforce a position in the group (Watson and Drew 2017). It also offers the speaker the opportunity to take a position of superiority, allowing an attack on others in a socially-acceptable way or enhancing self-esteem at the expense of others (Rodrigues and Collinson 1995).…”
Section: Humourmentioning
confidence: 99%
“…This study understands humour to be an "umbrella term" that covers a range of behaviour that is considered funny, such as wit, satire, and jokes (Lippitt 1994), but also incorporates improvised extended humorous sequences (Holmes et al 2007), and where participants themselves seemingly understand sequences of interaction to be humorous, such as where laughter was a central feature (Watson and Drew 2017). While a sense of humour is considered to be a relatively stable personality trait (Ruch 1998), within the literature the measurement of this construct remains problematic with a lack of measurement consistency (Martin 2003, Kong, Cooper andSosik 2019).…”
Section: Humourmentioning
confidence: 99%
See 1 more Smart Citation
“…Humor is complex, multifaceted and manifests as jokes, puns, funny stories, laughter, banter, teasing, satire, sarcasm, ironic remarks, ridicules, humorous behaviors and as a stimulus response, and as disposition (Martin, 2007). Chapman & Foot (1976) identified humor as a stimulus and any communication specifically intended to provoke laughter or smiling, and as a stimulus from the context of public speaking to convey critical information designed to elicit positive reactions (Watson & Drew, 2017;Markiewicz, 1974). Scholars have categorized types of humor as stimuli or described conditions under which humor may be experienced (Rybacki & Rybacki, 1991).…”
Section: Definitions and Theories Of Humormentioning
confidence: 99%
“…These studies confirm that humor helps define and maintain social groupings and reinforce both social and positional rankings (Boland & Hoffman, 1982;Duncan, 1982Duncan, , 1985. Robert & Wilbanks, (2012) and Watson & Drew (2017) observed that humor tend to be directed downward in a hierarchical organizational structure; that is, higher status persons tended to target lower status colleagues with their humor. Lundberg (1969) noted that lower-ranking group members tend not to joke back with higher status members.…”
Section: A Functional Perspective Of Humor In Communication and Tasksmentioning
confidence: 99%